2005
DOI: 10.1093/ndt/gfi189
|View full text |Cite
|
Sign up to set email alerts
|

Effects on inflammatory and nutritional markers of haemodiafiltration with online regeneration of ultrafiltrate (HFR) vs online haemodiafiltration: a cross-over randomized multicentre trial

Abstract: Haemodiafiltration with online regeneration of ultrafiltrate and online HDF are highly biocompatible techniques and no significant difference between HFR and online HDF was observed in terms of reduction of inflammatory markers. Further studies with a longer follow-up are needed to evaluate the clinical relevance of the online endogenous reinfusion to counteract the chronic inflammatory state of the uraemic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 19 publications
6
45
0
3
Order By: Relevance
“…Moreover, olHDF can remove proinflammatory substances such as cytokines (Bellomo et al, 1991;Lee et al, 2004). Again, we could confirm this phenomenon with lower CRP levels in the olHDF group vs. HD group (9.96+/-8.28 mgl/l vs. HD 16.07+/-16.26 mg/l, p=0.02), see Because albumin is a negative acute phase protein we can, in general, expect higher concentrations at lower inflammation (Panicchi et al, 2006;Kaysen et al, 1997). However, none-biocompatible membranes and partly low flux hemodialysis increases proinflammatory cytokines such as TNF-alpha.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, olHDF can remove proinflammatory substances such as cytokines (Bellomo et al, 1991;Lee et al, 2004). Again, we could confirm this phenomenon with lower CRP levels in the olHDF group vs. HD group (9.96+/-8.28 mgl/l vs. HD 16.07+/-16.26 mg/l, p=0.02), see Because albumin is a negative acute phase protein we can, in general, expect higher concentrations at lower inflammation (Panicchi et al, 2006;Kaysen et al, 1997). However, none-biocompatible membranes and partly low flux hemodialysis increases proinflammatory cytokines such as TNF-alpha.…”
Section: Discussionmentioning
confidence: 50%
“…Sin embargo, la sangre del paciente es sometida a procesos y materiales diferentes en ambas técnicas, y en la HFR además de la difusión y convección, interviene un proceso de adsorción 2,10 . El objetivo del presente estudio fue evaluar las diferencias entre la HDF-OL y la HFR en cuanto a parámetros clínicos, inflamatorios y de adecuación de la diálisis, así como respecto a su manejo por parte del personal de enfermería.…”
Section: Methodsunclassified
“…El tratamiento con hemodiálisis (HD) produce "per sé" un proceso inflamatorio crónico en el paciente, siendo este hecho, causa bien conocida de aumento de la morbimortalidad tanto global como de causa cardiovascular [1][2][3] . Este proceso inflamatorio mejora con la utilización de técnicas alternativas a la HD convencional como es la hemodiafiltración en línea (HDF-OL), que consigue mejorar los aclaramientos de toxinas urémicas al aumentar esta técnica el transporte convectivo [4][5][6] .…”
Section: Introductionunclassified
“…A number of clinical studies on ESRD patients have revealed that HFR remarkably improve dialytic efficiencies and solute removal over a wide molecular weight ranges, such as, the removal of uremic marker molecules ( 2M, leptin and free immunoglobulin light chains) (Bolasco et al, 2006, S. Kim et al, 2009, Testa et al, 2006, cardiovascular risk factors (homocysteine) (Splendiani et al, 2004), inflammatory cytokines (CRP, IL-1, IL-6), and biomarkers of oxidative stress (ox-LDL, IL-1 ) (Calo et al, 2011, Testa et al, 2006. In a comparison between HFR and on-line HDF, both were found to be highly biocompatible and to considerably reduce inflammatory markers, such as, CRP and IL-6 (Panichi et al, 2006). One technical variance of HFR is the repositioning of convection and diffusion.…”
Section: Paired Filtration Dialysis With Endogenous Reinfusion (Hfr)mentioning
confidence: 99%